2015
DOI: 10.1177/0333102415597891
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of sphenopalatine injection of onabotulinumtoxinA for the treatment of intractable chronic cluster headache

Abstract: ObjectiveThe main object of this pilot study was to investigate the safety of administering onabotulinumtoxinA (BTA) towards the sphenopalatine ganglion (SPG) in intractable chronic cluster headache. Efficacy data were also collected to provide indication on whether future placebo-controlled studies should be performed.MethodIn a prospective, open-label, uncontrolled study, we performed a single injection of 25 IU (n = 5) or 50 IU BTA (n = 5) towards the SPG in 10 patients with intractable chronic cluster head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 9 publications
5
63
0
3
Order By: Relevance
“…Other therapies with reports of efficacy in the treatment of CH that did not satisfy the inclusion criteria for our systematic review have been either recommended by other guidelines, discussed as therapeutic options in expert opinions, or reported in case series or open label studies . Such treatments include methysergide, methylergonovine, flunarizine, topiramate, gabapentin, baclofen, clonidine, pizotifen, histamine sulfate, kudzu, 2‐bromo lysergic acid diethylamide, hormonal therapies such as testosterone and clomiphene, as well as interventional therapies such as botulinum toxin injections, sphenopalatine ganglion blockade, and radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Other therapies with reports of efficacy in the treatment of CH that did not satisfy the inclusion criteria for our systematic review have been either recommended by other guidelines, discussed as therapeutic options in expert opinions, or reported in case series or open label studies . Such treatments include methysergide, methylergonovine, flunarizine, topiramate, gabapentin, baclofen, clonidine, pizotifen, histamine sulfate, kudzu, 2‐bromo lysergic acid diethylamide, hormonal therapies such as testosterone and clomiphene, as well as interventional therapies such as botulinum toxin injections, sphenopalatine ganglion blockade, and radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, an open‐label pilot study assessed the efficacy and safety of a single injection of 25‐50 units of onabotulinumtoxinA administered to the PPF under general anesthesia with preoperative imaging guidance in 10 patients using either a transnasal (n = 9) or percutaneous infrazygomatic (n = 1) approach in 10 patients with intractable chronic CH . In the intention to treat analysis, CH attack frequency at weeks 3 and 4 were reduced to 11 ± 14 from 18 ± 12 per week at baseline ( P = .038).…”
Section: Pathophysiologymentioning
confidence: 99%
“…) was used to perform the injection. In this pilot study, a significant reduction (≥50%) in CH attack frequency was observed in 5 out of 7 per‐protocol (PP) patients . After the pilot study, patients experiencing recurring attacks had access to repeated injections with minimal intervals of 3 months using the lateral injection technique (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…The sphenopalatine ganglion (SPG) is a large extracranial parasympathetic ganglion located in the pterygopalatine fossa and is thought to play a key role in CH pathogenesis . In a prospective, open‐label pilot study, our research group (Bratbak et al) performed blockade of the SPG with 25 to 50 IU onabotulinumtoxin type A (BTA) in 10 patients with CCH . The treatment was performed with a transnasal technique in 9 out of 10 subjects; in one subject a percutaneous infrazygomatic (lateral) approach was preferred due to anatomical anomalies.…”
Section: Introductionmentioning
confidence: 99%